Composition and diversity of arbuscular mycorrhizal fungi spore associated with different land-use types in tropical gold mine - Faisal Danu Tuheteru; H Husna; A Albasri; Asrianti Arif; Kartini Kramadibrata; Geofrey Soka (Brawijaya University, 2020)
Understanding the composition and diversity of arbuscular mycorrhizal fungi (AMF) is imperative for potentially enhancing their ecological role in different terrestrial ecosystems. Land use can have substantial effects on AMF species composition and diversity, but such effects have been explored less in tropical landscapes. In this study, we assessed the effects of disturbances on AMF species richness, observed the potential development of AMF types to produce mycorrhizal biofertilizer bioinoculants. This study was conducted identifying and selecting AMFs was for the purpose of managing post-mining land in Bombana District, Southeast Sulawesi, Indonesia. AMF spores collected from the field and trap culture were directly isolated and morphologically identified. A total of 15 AMF species were identified, including 11 species from field samples and 9 species from trap cultures. We noted that five AMF species were unique to field conditions and 5 AMF species were uniquely isolated from trap culture. It appears that Glomeraceae family contributed the highest number of species in all land-use types. Glomus sp. 1 was the most frequent species found in all land-use types. The Simpson’s index, Shannon index and evenness ranged from 1.60 ± 0.51 to 2.40 ± 0.40; 0.41 ± 0.17 to 0.62 ± 0.17; 0.25 ± 0.10 to 0.39 ± 0.11, respectively. In this study, we found three new records of AMF species including Entrophospora colombiana, Sclerocystis microcarpa and Glomus coronatum for Indonesia, i.e. from this study, it is clear that different land-use types affected AMF spore composition and species diversity. All AMF species found in this study were then applied to the land to improve land quality.